'To search and studdy out the secrett of tropical diseases by way of experiment'. - Warrell, D (2001)
William Harvey wrote about malaria, snake bite and rabies, three diseases now having their greatest impact in tropical developing countries. Global malarial mortality has not declined for 50 years. The most effective control measure would be a vaccine. Temporary immunity in humans, through hundreds of bites by irradiated infected mosquitoes, was achieved in the 1970s. A promising current strategy is effector T-cell vaccination directed at infected hepatocytes. RTS,S/(SB)ASO2, an adjuvanted fusion protein, produced transient protection in 70% of vaccines. Prime (DNA vaccine) boost (poxvirus recombinant) is particularly immunogenic. Pyrethroid-treated bed nets reduce childhood mortality and deplete the mosquito population, interrupting transmission. Chlorproguanil-dapsone is more effective than pyrimethamine-sulfadoxine in treating uncomplicated chloroquine-resistant malaria. Artemisinin derivatives are as effective as quinine in severe disease. Snake bite is an underestimated and neglected cause of morbidity and mortality in rural communities in tropical countries. Sutherland's pressure-immobilisation technique is recommended first-aid for victims of neurotoxic elapid snakes. Rabies post-exposure prophylaxis, using new generation cell culture vaccines, is now feasible in developing countries, employing an economical 8-site intradermal regimen. This Harveian Oration, the first in 350 years to be devoted to tropical medicine, emphasises the importance of this speciality in the twenty-first century.